A Polynomial of Pulmonary Tuberculosis Patients Showing the Behaviour Using the Lagrange`S Method - Rajan Singh, B. K. Singh, Anshul Dubey, Nidhi Tiwari (Mathematical Statistician and Engineering Applications, 2022)
In the new modern society, Pulmonary Tuberculosis is a serious, chronic disease. Tuberculosis may infect any part of the body, but most commonly occurs in the lungs (known as pulmonary tuberculosis). Extrapulmonary TB occurs when tuberculosis develops outside of the lungs, although extrapulmonary TB may coexist with pulmonary TB. In this research paper, the aim of this study is to find the suitable polynomial equation of the pulmonary Tuberculosis patients with the variable (x) for the unequal interval of SPO2 level.